Novel bimetallic tin-manganese oxides-carbon nanotube nanocomposite and their charge storage properties - Chiang, Ng Kok, Ir. Dr (The Institution of Engineers, Malaysia (IEM), 2014)
Link to publisher’s homepages at http://www.myiem.org.my/